Presentation of a Quantitative Model of Factors Affecting Earnings Management: Focusing on Managers’ Opportunistic Manipulations of Discretionary Accruals - Saadati, Ehsan; Yazdani, Shohreh; Khanmohammadi, MohammadHamed; Gorjizadeh, Davoud (Business, Marketing, and Finance Open, 2024)
The present study is based on providing a quantitative model of factors influencing earnings management, with a focus on managers' opportunistic manipulations of discretionary accruals. This research follows a mixed-methods approach and is classified as sequential and embedded in nature. Based on the reasoning logic, this study falls under the category of "deductive and inductive" research and has been conducted in two stages. The first stage is fundamental, while the second stage is applied. This study belongs to the category of original (first-hand) research and, from a methodological perspective, is classified as descriptive. Given that data collection in this research was conducted naturally and without intervention in both stages, it falls under non-experimental (descriptive) studies. From a temporal perspective, it is retrospective, and in terms of duration, it is cross-sectional. Based on the findings derived from the quantitative model, weaknesses in the accounting system, issues related to owners and shareholders, managerial incentives (such as knowledge-based and personality-driven motivations), internal organizational conditions, and external environmental factors have been identified as the five primary factors influencing earnings management through discretionary accrual manipulation.